The impact of a terrorist attack: Survivors’ health, functioning and need for support following the 2019 Utrecht tram shooting 6 and 18 months post-attack - Bosmans, Mark W. G.; Plevier, Carolien; Schutz, Francoise; Stene, Lise E.; Yzermans, C. Joris; Dückers, Michel L. A. (Frontiers in Psychology, 2022)
Background: Extremely violent events such as terrorist attacks and mass shootings form a severe risk for the health and wellbeing of affected individuals. In this study based on a public health monitor, we focus on the health impact (including PTSD symptoms, physical problems and day-to-day functioning) of the Utrecht tram shooting, which took place in the morning of March 18th 2019. A lone gunman opened fire on passengers within a moving tram. Four people died, and six people were injured in this attack. The attack resulted in nationwide commotion and drew much media attention. Aim of this study was to increase insight into the health effects for the survivors (those directly impacted by a terrorist attack and the bereaved), and whether they received the needed care and support. Methods: Semi-structured interviews with accompanying questionnaires were conducted at six and 18 months post-attack. Overall, 21 survivors (victims/witnesses and loved ones of deceased victims) participated in the first series of interviews, 15 in the second series. Qualitative data were analyzed using reflexive thematic analysis, quantitative data was only described because of the low sample size. Results: At both six and 18 months after the attack many survivors had been able to resume daily life, and most rated their overall health as (very) good or excellent. At the same time, a substantial portion suffered from health problems such as posttraumatic stress symptoms and other complaints, and needed professional care. Furthermore, those in need did not always find their own way to appropriate care through the existing health system: half of the survivors still needed support in finding the right care 18 months later. Conclusions: Although the design and implementation of this public health monitor were accompanied by multiple challenges, it was possible to track a portion of the survivors and gain insight in the considerable health burden of the attack. Also, it is clear in this study that the health impact of terrorism affects survivors in the long run and requires attention from health authorities and professionals, as survivors were not able to find the right care by themselves.